2020
DOI: 10.1155/2020/5742569
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment to Illness and Its Relationship with Spiritual Wellbeing in Iranian Cancer Patients

Abstract: Background. The aim of this study was to investigate the psychosocial adjustment to illness and its relation with spiritual health in cancer patients. Methods. This study was conducted in 2019 in Iran. It was a descriptive study with a sample of 124 cancer patients. Data were collected using two questionnaires of the psychosocial adjustment to illness scale (PAIS) with 46 questions and the Paloutzian and Ellison spiritual health scale with 20 questions. Results. The mean age of the participants in this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The Persian version of this questionnaire has appropriate validity and reliability and has been frequently used in Iranian patients. [16][17][18]…”
Section: The Ellison-paloutzian Spiritual Well-being Scalementioning
confidence: 99%
“…The Persian version of this questionnaire has appropriate validity and reliability and has been frequently used in Iranian patients. [16][17][18]…”
Section: The Ellison-paloutzian Spiritual Well-being Scalementioning
confidence: 99%
“…Our study participants’ scores were slightly higher than those of a population of patients with cancer surveyed in Iran. 25 Meanwhile, the psychosocial adjustment problems of our Chinese CRC survivors were milder than those of Korean CRC survivors, who were surveyed in a study that included patients with longer survivorship and of all ages. 7 Nineteen percent of their participants had severe maladjustment, indicating that psychosocial adjustment among CRC survivors requires attention and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study conducted in South Korea indicated that patients had good psychological adjustment [9]. Senmar M (2020) believed that psychological adjustment differs among patients with different demographic characteristics, cultural and social support [10]. Patients in different countries and ethnic groups also had different concepts of psychological adjustment [3].…”
Section: Level Of Psychological Adjustment Among Patients With Ostomymentioning
confidence: 99%
“…Ayik C indicated that age was one of the most significant factors affecting the meaning and hope components [13]. Senmar M found that education level and economic status were related to psychological adjustment, in which increasing patient education level and better economic status led to a lower score of psychosocial adjustment [10]. According to some studies, social relationships and support from a partner or family member are important to patients with ostomies [11].…”
Section: Factors Associated With the Level Of Psychological Adjustmen...mentioning
confidence: 99%